Sensor Actuator Network for In Situ Studies of Antarctic Plants Physiology - Krzysztof Herman; Mauricio Montanares; Leon Bravo; Joanna Plenzler (Sensors, 2022)
This article documents a custom sensor–actuator network designed and implemented as a part of experimental setup, where a long-term phenological response of antarctic plants is studied. The first part of our work presents the context of the study, reports experimental methods used in antarctic plant field studies, and characterizes the environmental conditions and logistics facilities available on the measurement spot. After contextualization of the research, we present, in detail, both the network itself and some results obtained during the Antarctic summer seasons between 2019 and 2022 on the King George Island, South Shetlands. The results collected with our network and correlated with selected data registered with a reference automatic meteorological station reveal the thermal plants response. The groups of plants individuals, which were actively warmed using thermal actuators, show the nighttime temperature difference, in reference to the air temperature, of 5 ∘C, which complements the daytime difference caused by the passive method of open top chamber (OTC) used in previous studies carried out in the same localization.